From Access to Behavior: How Digital Financial Inclusion Shapes Sustainable Financial Practices via Cognitive Financial Framing among Coastal MSMEs - Martha Racwel Patty (West Science Journal Economic and Entrepreneurship, 2026)
This study examines how digital financial inclusion influences sustainable financial practices through cognitive financial framing among coastal MSMEs in Maluku. Although access to digital financial services has expanded significantly, many MSMEs still struggle to translate this access into disciplined and long-term financial behavior. This research adopts a quantitative explanatory approach using data from 342 respondents and analyzes the relationships using SEM-PLS. The findings reveal that digital financial inclusion has a significant positive effect on cognitive financial framing, which in turn strongly influences sustainable financial practices. While digital financial inclusion also directly affects financial behavior, its impact is weaker compared to the indirect effect through cognitive mechanisms. These results indicate that access alone is insufficient to drive behavioral change without adequate cognitive capacity in managing financial resources. The study highlights the importance of integrating behavioral finance perspectives, particularly the Behavioral Life-Cycle Hypothesis, to explain how financial decisions are shaped over time. The findings provide both theoretical and practical implications for designing more effective financial inclusion policies.